2022
DOI: 10.1021/acs.est.2c03653
|View full text |Cite
|
Sign up to set email alerts
|

Compensation or Aggravation: Pb and SO2 Copoisoning Effects over Ceria-Based Catalysts for NOx Reduction

Abstract: Severe catalyst deactivation caused by multiple poisons, including heavy metals and SO2, remains an obstinate issue for the selective catalytic reduction (SCR) of NO x by NH3. The copoisoning effects of heavy metals and SO2 are still unclear and irreconcilable. Herein, the unanticipated differential compensated or aggravated Pb and SO2 copoisoning effects over ceria-based catalysts for NO x reduction was originally unraveled. It was demonstrated that Pb and SO2 exhibited a compensated copoisoning effect over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Subsequently, the adsorbed NH 3 species are gradually consumed after the introduction of 1000 ppm of NO and 5% O 2 , absorption bands corresponding to H 2 O appear around 1630 cm –1 as well as 3500 cm –1 (Figure S32), and adsorbed NO x species are hardly observed in the first 4 min of the SCR reaction when the NH 3 band intensity is significantly reduced, indicating that the adsorbed NH 3 reacts with gaseous NO at this time, i.e., the reaction follows the E-R mechanism. Finally, the surface of the Mn/ZrTi-A catalyst is covered by monodentate nitrate (1244 cm –1 ), adsorbed NO x (1590, 1619 cm –1 ), and a small amount of bidentate nitrate (1552 cm –1 ) . As for Mn/ZrTi-C (Figure b), the absorption bands at 1204, 1603, and 1435 cm –1 appear after preadsorption of NH 3 at 120 °C for 60 min, corresponding to NH 3 and NH 4 + species, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Subsequently, the adsorbed NH 3 species are gradually consumed after the introduction of 1000 ppm of NO and 5% O 2 , absorption bands corresponding to H 2 O appear around 1630 cm –1 as well as 3500 cm –1 (Figure S32), and adsorbed NO x species are hardly observed in the first 4 min of the SCR reaction when the NH 3 band intensity is significantly reduced, indicating that the adsorbed NH 3 reacts with gaseous NO at this time, i.e., the reaction follows the E-R mechanism. Finally, the surface of the Mn/ZrTi-A catalyst is covered by monodentate nitrate (1244 cm –1 ), adsorbed NO x (1590, 1619 cm –1 ), and a small amount of bidentate nitrate (1552 cm –1 ) . As for Mn/ZrTi-C (Figure b), the absorption bands at 1204, 1603, and 1435 cm –1 appear after preadsorption of NH 3 at 120 °C for 60 min, corresponding to NH 3 and NH 4 + species, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…(002) = −1.80 eV since the more negative value indicated stronger adsorption according to previous research. 66,67 Interestingly, this interaction of CeO 2−x and SO 4 tended to occur at the oxygen vacancy sites rather than at the neighboring Ce as the sulfate ion would spontaneously move to the oxygen vacancy sites during the geometric optimization process. All of the calculated results are provided in Table 2.…”
Section: Theoretical Perspective Of the Sulfationmentioning
confidence: 99%
“…Previously, Zhang et al found that the copoisoning of K and phosphorus exhibited a detoxification effect on Fe 2 O 3 /TiO 2 catalysts due to the newly formed Brønsted acid sites provided by phosphate and the enhanced redox ability originated mainly from the Fe–O–P structure. The detoxification effects of heavy metals and phosphorus or SO 2 were also demonstrated on CeO 2 /TiO 2 catalysts. , However, the copoisoning mechanisms for V-based catalysts in the coexistence of arsenic and cadmium are barely explored.…”
Section: Introductionmentioning
confidence: 99%
“…The detoxification effects of heavy metals and phosphorus or SO 2 were also demonstrated on CeO 2 /TiO 2 catalysts. 29,30 However, the copoisoning mechanisms for V-based catalysts in the coexistence of arsenic and cadmium are barely explored. In this work, the detoxification effect of arsenic on the cadmium-poisoned V 2 O 5 /TiO 2 (VTi) catalyst was reported.…”
Section: Introductionmentioning
confidence: 99%